Analisis determinan konsumsi petani kelapa sawit di Desa Pulau Tujuh Kecamatan Pamenang Barat Kabupaten Merangin - Nurwahyu Ningsih, Endah; Rahmadi, Selamet; Umiyati, Etik (Jurnal Paradigma Ekonomika, 2024)
This study aims to (1) To find out and analyze the social and economic conditions of oil palm farmers (2) To find out and analyze factors that affect income, the number of family dependents, education and age on farmers' consumption in Pulau Tujuh Village, West Pamenang District, Merangin Regency. The analysis methods used in this study are descriptive analysis and quantitative analysis using analysis tools, namely multiple linear regression. The sampling technique used proportional random sampling of 82 oil palm farmers. Data collection techniques are carried out by interviews and questionnaires. The results of the study showed that income and the number of family dependents were significant to the consumption of oil palm farmers while the variables of education and age were not significant to the consumption of oil palm farmers in Pulau Tujuh Village, West Pamenang District, Merangin Regency.